Stabilizer for cyanide-free gold-plated tin alloy, gold-plated tin alloy liquid and preparation method of gold-plated tin alloy liquid

By using 4-hydroxyphenylphenethylamine and 2-methyl-8-hydroxyquinoline as stabilizers in the cyano-free gold plating tin alloy process, combined with other components, the problem of poor stability of the plating solution is solved, and the long-term plating solution is realized Stable use and high-quality output of coating.

CN119265654APending Publication Date: 2025-01-07CHONGQING LIDAO SURFACE TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411690031.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The plating solution has poor stability in the existing cyanide-free gold-plating tin alloy process, resulting in frequent instability of the plating solution, which increases process cost and inhibits the application of the process.

Method used

Using 4-hydroxyphenylphenethylamine and 2-methyl-8-hydroxyquinoline as stabilizers, the stability of the plating solution is improved by inhibiting the oxidation of tin ions and the composition changes of alloy plating layer, and chlorine is added to the plating solution. Sodium gold, sodium sulfite, ethylenediaminetetraacetic acid, potassium pyrophosphate, ammonium citrate, hydroquinone and silicone oil form a stable gold-plated tin alloy liquid.

Benefits of technology

It significantly improves the stability of the gold-plated tin alloy liquid, extends the use time, ensures the uniformity and appearance quality of the plating layer, reduces the generation of precipitates, and reduces the process cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265654A_ABST
    Figure CN119265654A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of gold-tin alloy electroplating, in particular to a stabilizer for cyanide-free gold-tin alloy plating, a gold-tin alloy plating solution and a preparation method of the cyanide-free gold-tin alloy plating solution. The concentration of the 2-methyl-8-hydroxyquinoline is 0.05 g / L-2. 5 g / L; the stability of the gold-plated tin alloy liquid can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gold-tin alloy electroplating, and in particular to a cyanide-free gold-tin alloy plating stabilizer, a gold-tin alloy plating liquid and a preparation method thereof. Background Art

[0003] Gold-tin alloy, also known as gold-tin eutectic (Au-Sn), is a plating solution in which the gold ions and stannous ions are deposited on the workpiece through electrolysis at a mass fraction of 80% Au and 20% tin. The gold-tin alloy electroplating on the market is divided into two directions: cyanide plating and cyanide-free plating. The cyanide plating solution has high stability, but the toxic substance CN- exists in the plating solution, which is very harmful to the human body and does not meet the needs of green environmental protection and sustainable development.

[0004] The research and application of cyanide-free electroplating technology at home and abroad started in the 1960s, but it has developed slowly. Although gold-tin alloy plating solutions of sulfite system and citrate system have been developed, the technology is not mature. The main advantages of these processes are sustainable development and environmental friendliness, and their disadvantages are poor stability of the plating solution. The divalent tin in the plating solution will be continuously oxidized and hydrolyzed into tetravalent tin due to contact with air. When the concentration of tetravalent tin exceeds the upper limit, precipitation will occur, causing the plating solution to become unstable. At this time, the bath solution must be replaced, which invisibly increases the process cost, thereby inhibiting the application of cyanide-free gold-tin alloy plating technology.

[0005] Therefore, those skilled in the art are committed to developing a cyanide-free gold-tin alloy stabilizer, a gold-tin alloy plating solution and a preparation method thereof to improve the stability of the gold-tin alloy plating solution. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide a cyanide-free gold-tin alloy plating stabilizer, a gold-tin alloy plating liquid and a preparation method thereof, so as to improve the stability of the gold-tin alloy plating liquid. The technical solution of the present invention to solve the above technical problems is as follows: A stabilizer for cyanide-free gold-tin alloy plating, comprising the following raw materials and weight concentrations: 0.15 g / L-5 g / L of 4-hydroxyphenylethylamine; 2-Methyl-8-hydroxyquinoline 0.05g / L -2.5g / L.

[0008] The beneficial effect of adopting the above scheme is that the 4-hydroxyphenylethylamine contained in the stabilizer of the gold-tin alloy can effectively inhibit the oxidation of Sn2+ in the plating solution to Sn4+, making the structure of the tin ions more stable during the electroplating reaction, thereby preventing the formation of precipitates in the plating solution, and further improving the stability of the plating solution, while 2-methyl-8-hydroxyquinoline can inhibit the alloy coating composition from changing with the passage of time and the change of cathode current density, play a role in stabilizing the alloy coating, and is conducive to obtaining a uniform, dense and good-looking coating.

[0009] Based on the above technical solution, the present invention can also be improved as follows.

[0010] Furthermore, the mass ratio of the 4-hydroxyphenylethylamine to 2-methyl-8-hydroxyquinoline is 2-3:1.

[0011] The beneficial effect of adopting the above further scheme is that the appropriate proportion of 4-hydroxyphenylethylamine and 2-methyl-8-hydroxyquinoline reduces the generation of precipitates and improves the stability of the gold-tin alloy plating solution.

[0012] A gold-tin alloy plating solution includes the cyanide-free gold-tin alloy plating stabilizer as described above, and also includes the following raw materials and weight concentrations: Sodium gold chloride 5 g / L -10g / L, stannous chloride dihydrate 3g / L -5g / L, sodium sulfite 50g / L -80g / L, ethylenediaminetetraacetic acid 3g / L -7g / L, potassium pyrophosphate 30g / L -60g / L, ammonium citrate 50g / L -70g / L.

[0013] The beneficial effect of adopting the above further scheme is: the present application effectively improves the stability of the gold-tin alloy plating solution by adding a stabilizer composed of 4-hydroxyphenethylamine and 2-methyl-8-hydroxyquinoline, and the plating solution can be stably used for more than 8 cycles without affecting the deposition rate and the crystallization of the coating. The appropriate proportion of 4-hydroxyphenethylamine and 2-methyl-8-hydroxyquinoline reduces the formation of precipitates, improves the stability of the gold-tin alloy plating solution, and extends the use time of the gold-tin alloy plating solution.

[0014] Furthermore, the raw materials also include 3 g / L to 7 g / L of hydroquinone and silicone oil, and the thickness of the silicone oil floating on the surface of the electrolyte is 100 nm to 200 nm.

[0015] The beneficial effects of adopting the above further scheme are: hydroquinone is used to react with oxygen in the electrolyte to reduce the oxygen content in the electrolyte, silicone oil reduces the contact between the electrolyte and the external air and absorbs dust in the air to reduce the entry of dust into the electrolyte.

[0016] A method for preparing a gold-tin alloy plating solution, applied to the gold-tin alloy plating solution as described above, comprises the following steps: S100. Weigh sodium gold chloride particles, stannous chloride dihydrate particles, stannous chloride dihydrate particles, stannous chloride dihydrate particles, potassium pyrophosphate particles, ammonium citrate, 4-hydroxyphenylethylamine particles and 2-methyl-8-hydroxyquinoline particles according to the mass ratio of the gold-tin alloy plating liquid components; S200. Under constant temperature conditions, after adding deionized water to the mixing container, the solid particles weighed in step S100 are dissolved in the deionized water in sequence, and stirred continuously; S300. Add deionized water to the mixing container and adjust the volume to a specified concentration.

[0017] The beneficial effect of adopting the above further scheme is: after accurately weighing various raw materials, dissolving them in deionized water and fixing the volume to a specified concentration, the preparation efficiency of the tin-gold alloy solution is improved.

[0018] Further, in step S100, the preparation of 2-methyl-8-hydroxyquinoline comprises the following steps: S111. Add o-aminophenol to the hydrochloric acid solution and stir under reflux, the weight volume ratio of o-aminophenol to hydrochloric acid is 11 g: 40 mL-60 mL, and the concentration of hydrochloric acid is 16%-20%; S112. Add a mixed solution of o-nitrophenol and crotonaldehyde dropwise to step S111, reflux for 1.5h to 3h and then cool to room temperature, the weight volume ratio of o-nitrophenol to crotonaldehyde is 1g: 2ml-4ml, and the dropping speed is 0.15mol / h-0.25mol / h; S113. After adding excess ammonia to the cooled mixed solution in step S112, dichloromethane was added for extraction and the lower layer of solution was removed, followed by ultrasonic drying; S114. The solvent dried in step S113 is distilled under reduced pressure, and the fraction at 149°C to 155°C / 246 Pa is collected and cooled to obtain 2-methyl-8-hydroxyquinoline solid.

[0019] The beneficial effect of adopting the above further scheme is: improving the preparation efficiency of 2-methyl-8-hydroxyquinoline.

[0020] Furthermore, in step S112, after placing the o-aminophenol and hydrochloric acid solution in a magnetic field, a mixed solution of o-nitrophenol and crotonaldehyde is added dropwise to the mixed solution.

[0021] The beneficial effects of adopting the above further scheme are: the magnetic field increases the reaction rate of the solution, and the intermediate product, under the action of the magnetic field, accelerates the reaction rate, affects the product selectivity, induces new reaction paths, and increases the success rate of the final product.

[0022] Furthermore, in step S114, when the solution is distilled under reduced pressure to produce the 2-methyl-8-hydroxyquinoline solid, ultrasonic waves are emitted into the distillation apparatus.

[0023] The beneficial effect of adopting the above further scheme is that the high-frequency micro-vibration of ultrasound can destroy the layered structure of the surface of the distilled liquid, increase the effective area of ​​the interface, thereby increasing the mass transfer rate between substances, increasing the activity of the reactant molecules, and accelerating the vaporization rate of the liquid, thereby improving the distillation efficiency, while avoiding the destruction of the original molecular structure in a high temperature environment.

[0024] Further, in step S100, the preparation of 4-hydroxyphenylethylamine comprises the following steps: S121. In the reaction apparatus, p-methoxybenzaldehyde, methanol, anhydrous sodium acetate, and nitromethane are sequentially added, wherein the addition ratio of methoxybenzaldehyde, methanol, anhydrous sodium acetate, and nitromethane is 8mol-12mol: 6L-10L: 1.5mol-2.5mol: 13mol-17mol, and the reaction is continued for 5h to 7h, and crystallization is performed at low temperature, and the crystals are filtered and dried to obtain; S122. Add the crystals obtained in step S121 to a reaction device, and then add anhydrous ethanol, concentrated hydrochloric acid and palladium carbon in sequence, and introduce hydrogen gas to react until the nitro group is completely reacted to obtain a primary solution; The addition ratio of crystal, anhydrous ethanol, concentrated hydrochloric acid and palladium carbon is 0.8mol-1.2mol:9L-11L:180ML-230ML:140g-160g; S123. Filter the primary solution in step S122 to remove the catalyst, and then distill to obtain 4-hydroxyphenethylamine.

[0025] The beneficial effect of adopting the above further scheme is: improving the preparation efficiency of 4-hydroxyphenylethylamine.

[0026] Furthermore, in step S121, methoxybenzaldehyde, methanol, anhydrous sodium acetate, and nitromethane are in an ultrasonic environment when reacting in the reaction device.

[0027] The beneficial effect of adopting the above further scheme is that the ultrasonic wave increases the activity of the reactant molecules and accelerates the reaction speed.

[0028] Furthermore, in step S121, low-temperature freeze drying is used to obtain anhydrous crystals when drying the crystals.

[0029] The beneficial effect of adopting the above further scheme is that low temperature freezing avoids destroying the original molecular structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The figure is a flowchart of a specific embodiment of the present invention. DETAILED DESCRIPTION

[0031] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0032] In the description of the present invention, it is necessary to understand that the terms "center", "length", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "inside", "outside", "peripheral", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred system or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0033] In the description of the present invention, “plurality” means at least two, for example, two, three, etc., unless otherwise clearly and specifically defined.

[0034] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0035] A stabilizer for cyanide-free gold-tin alloy plating comprises the following raw materials and weight concentrations: 0.15 g / L-5 g / L 4-hydroxyphenylethylamine; 0.05 g / L-2.5 g / L 2-methyl-8-hydroxyquinoline.

[0036] In other embodiments, the mass ratio of 4-hydroxyphenethylamine to 2-methyl-8-hydroxyquinoline is 2-3:1.

[0037] The present invention also provides a gold-tin alloy plating solution, comprising the stabilizer for cyanide-free gold-tin alloy plating as described above, and also comprising the following raw materials and weight concentrations: Sodium gold chloride 5 g / L -10g / L, stannous chloride dihydrate 3g / L -5g / L, sodium sulfite 50g / L -80g / L, ethylenediaminetetraacetic acid 3g / L -7g / L, potassium pyrophosphate 30g / L -60g / L, ammonium citrate 50g / L -70g / L, hydroquinone 3g / L -7g / L.

[0038] Specifically, in order to test the effect of the stabilizer in cyanide-free gold-tin alloy plating solution, the coating appearance, plating solution stability and other tests were tested, including: Number of cycles: Each replenishment of the gold salt and tin salt for the initial tank is one cycle; Coating appearance inspection: It is carried out visually under natural scattered light source or white projection light without reflected light. The test piece should be placed 1.2m~1.5m away from the object under the irradiation of 40W fluorescent lamp, and the eyes should be observed at a distance of 35cm±5cm from the part to observe whether the overall appearance of the test piece is uniform and consistent, whether the coating is crystallized and fine, and whether there is any blackening or roughness.

[0039] Plating solution stability test: prepare 100mL of plating solution for electrolytic consumption, and observe whether the plating solution has decomposition, precipitation, discoloration, etc.

[0040] Example 1 The present embodiment 1 provides a cyanide-free gold-tin alloy plating solution containing a stabilizer, including the following mass concentrations: 0.15 g / L 4-hydroxyphenylethylamine, 0.05 g / L 2-methyl-8-hydroxyquinoline, 10 g / L sodium gold chloride, 5 g / L stannous chloride dihydrate, 60 g / L sodium sulfite, 5 g / L ethylenediaminetetraacetic acid, 40 g / L potassium pyrophosphate, 60 g / L ammonium citrate, and 5 g / L hydroquinone.

[0041] In this example, the prepared cyanide-free gold-tin alloy plating solution containing a stabilizer is subjected to a performance test while introducing a cyanide-free gold-tin alloy plating solution (whose mass concentration is the same as that of the cyanide-free gold-tin alloy plating solution in Example 1, except that no stabilizer is added) as a comparison, as shown in the following.

[0042] Select a 50×50×1mm copper specimen for plating (electroplating parameters: current density 1A / dm 2 , temperature 50℃, pH value controlled between 7-8, ratio of anode to cathode area greater than 2:1, platinum-plated titanium anode is used as anode plate), replace the copper sheet every 30 minutes of electroplating. During this process, it is necessary to observe whether the state of the coating is normal, whether there is precipitation, discoloration and other abnormal conditions in the plating solution, and at the same time analyze and record the amount of main salt added to the plating solution.

[0043] The test results are shown in Table 1 and Table 2, specifically: Number of cycles Coating appearance Bath state 1 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 3 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 5 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 8 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation Table 1 Plating cycle test results of cyanide-free gold-tin alloy plating solution containing stabilizer Number of cycles Coating appearance Bath state 1 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 3 Fine crystals, uniform bright golden yellow Beginning to become turbid 5 The coating appears dark The color of the plating solution becomes darker and turbid Table 2 Effect of cyanide-free gold-tin alloy plating cycle test From the data in Table 1 and Table 2, it can be seen that when the cyanide-free gold-tin alloy plating solution containing a stabilizer in the present application is used for electroplating, the coating of the electroplated part obtained in Example 1 is uniform, delicate and bright golden yellow, and the plating solution is continuously used for 8 cycles without color change, clear and transparent, and no precipitation is produced; and when the cyanide-free gold-tin alloy plating solution is used for electroplating, the coating is uniform, delicate and bright golden yellow in the first 3 cycles, and the coating begins to darken after 3 cycles, and the color of the plating solution becomes darker and turbid; in summary, the cyanide-free gold-tin alloy plating solution after adding a stabilizer effectively improves the stability of the plating solution during the electroplating process, and the generated electroplated layer is finely crystalline and still has a good appearance.

[0044] Example 2 The present embodiment provides a cyanide-free gold-tin alloy plating solution containing a stabilizer, including mass concentrations of: 0.5 g / L 4-hydroxyphenylethylamine, 0.1 g / L 2-methyl-8-hydroxyquinoline, 8 g / L sodium gold chloride, 5 g / L stannous chloride dihydrate, 70 g / L sodium sulfite, 5 g / L ethylenediaminetetraacetic acid, 50 g / L potassium pyrophosphate, 60 g / L ammonium citrate, and 5 g / L hydroquinone.

[0045] In this example, the prepared cyanide-free gold-tin alloy plating solution containing a stabilizer is subjected to a performance test while introducing a cyanide-free gold-tin alloy plating solution (whose mass concentration is the same as that of the cyanide-free gold-tin alloy plating solution in Example 1, except that no stabilizer is added) as a comparison, as shown in the following.

[0046] Select a 50×50×1mm copper specimen for plating (electroplating parameters: current density 1A / dm 2 , temperature 50℃, pH value controlled between 7-8, ratio of anode to cathode area greater than 2:1, platinum-plated titanium anode is used as anode plate), replace the copper sheet every 30 minutes of electroplating. During this process, it is necessary to observe whether the state of the coating is normal, whether there is precipitation, discoloration and other abnormal conditions in the plating solution, and at the same time analyze and record the amount of main salt added to the plating solution.

[0047] The test results are shown in Table 3 and Table 4, specifically: Number of cycles Coating appearance Bath state 1 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 3 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 5 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 8 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation Table 3 Plating cycle test results of cyanide-free gold-tin alloy solution containing stabilizer Number of cycles Coating appearance Bath state 1 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 3 Fine crystals, uniform bright golden yellow The color of the plating solution becomes darker and clearer 5 Fine crystals, uniform bright golden yellow The plating solution becomes turbid Table 4 Effect of cyanide-free gold-tin alloy plating cycle test From the data in Table 3 and Table 4, it can be seen that when the cyanide-free gold-tin alloy plating solution containing a stabilizer in the present application is used for electroplating, the coating of the electroplated part obtained in Example 2 is uniform, delicate and bright golden yellow, and the plating solution is continuously used for 8 cycles without color change, clear and transparent, and no precipitation is produced; and when the cyanide-free gold-tin alloy plating solution is used for electroplating, within the first 3 cycles, the coating is uniform, delicate and bright golden yellow, the plating solution is clear and transparent, and the plating solution begins to become turbid in the 5th cycle; in summary, it can be seen that the cyanide-free gold-tin alloy plating solution after adding a stabilizer effectively improves the stability of the plating solution during the electroplating process, and the generated electroplated layer is finely crystalline and has a good appearance.

[0048] Example 3 The present embodiment provides a cyanide-free gold-tin alloy plating solution containing a stabilizer, including mass concentrations of: 1 g / L 4-hydroxyphenylethylamine, 0.3 g / L 2-methyl-8-hydroxyquinoline, 10 g / L sodium gold chloride, 5 g / L stannous chloride dihydrate, 60 g / L sodium sulfite, 5 g / L ethylenediaminetetraacetic acid, 45 g / L potassium pyrophosphate, 60 g / L ammonium citrate, and 5 g / L hydroquinone.

[0049] In this example, the prepared cyanide-free gold-tin alloy plating solution containing a stabilizer is subjected to a performance test while introducing a cyanide-free gold-tin alloy plating solution (whose mass concentration is the same as that of the cyanide-free gold-tin alloy plating solution in Example 3, except that no stabilizer is added) as a comparison, as shown in the following.

[0050] Select a 50×50×1mm copper specimen for plating (electroplating parameters: current density 1A / dm 2 , temperature 50℃, pH value controlled between 7-8, ratio of anode to cathode area greater than 2:1, platinum-plated titanium anode is used as anode plate), replace the copper sheet every 30 minutes of electroplating. During this process, it is necessary to observe whether the state of the coating is normal, whether there is precipitation, discoloration and other abnormal conditions in the plating solution, and at the same time analyze and record the amount of main salt added to the plating solution.

[0051] The test results are shown in Table 5 and Table 6, specifically: Number of cycles Coating appearance Bath state 1 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 3 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 5 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 8 Fine crystals, uniform bright golden yellow, gloss slightly reduced Colorless, clear and transparent, no precipitation Table 5 Plating cycle test results of cyanide-free gold-tin alloy plating solution containing stabilizer Number of cycles Coating appearance Bath state 1 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 3 Fine crystals, uniform bright golden yellow The plating solution becomes turbid 5 Fine crystallization, reduced gloss of coating The plating solution has precipitation and the color becomes darker Table 6 Effect of cyanide-free gold-tin alloy plating cycle test From the data in Table 5 and Table 6, it can be seen that when the cyanide-free gold-tin alloy plating solution containing a stabilizer in the present application is used for electroplating, the coating presents a delicate and bright golden color in the first 5 cycles, the glossiness of the coating decreases slightly in the 10th cycle, and the plating solution is clear, colorless and transparent in the first 10 cycles without precipitation; and when the cyanide-free gold-tin alloy plating solution is used for electroplating, the coating presents a uniform, delicate and bright golden color in the first 5 cycles, and the plating solution begins to become turbid in the 3rd cycle, and the color of the plating solution becomes darker; In summary, the cyanide-free gold-tin alloy plating solution with the addition of a stabilizer effectively improves the stability of the plating solution during the electroplating process, and has a better appearance.

[0052] Example 4 The present embodiment provides a cyanide-free gold-tin alloy plating solution containing a stabilizer, including mass concentrations of: 1.5 g / L 4-hydroxyphenylethylamine, 0.5 g / L 2-methyl-8-hydroxyquinoline, 10 g / L sodium gold chloride, 4 g / L stannous chloride dihydrate, 80 g / L sodium sulfite, 5 g / L ethylenediaminetetraacetic acid, 40 g / L potassium pyrophosphate, 60 g / L ammonium citrate, and 5 g / L hydroquinone.

[0053] In this example, the prepared cyanide-free gold-tin alloy plating solution containing a stabilizer is subjected to a performance test while introducing a cyanide-free gold-tin alloy plating solution (whose mass concentration is the same as that of the cyanide-free gold-tin alloy plating solution in Example 4, except that no stabilizer is added) as a comparison, as shown in the following.

[0054] Select a 50×50×1mm copper specimen for plating (electroplating parameters: current density 1A / dm 2 , temperature 50℃, pH value controlled between 7-8, ratio of anode to cathode area greater than 2:1, platinum-plated titanium anode is used as anode plate), replace the copper sheet every 30 minutes of electroplating. During this process, it is necessary to observe whether the state of the coating is normal, whether there is precipitation, discoloration and other abnormal conditions in the plating solution, and at the same time analyze and record the amount of main salt added to the plating solution.

[0055] The test results are shown in Table 7 and Table 8, specifically: Number of cycles Coating appearance Bath state 1 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 3 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 5 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 8 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation Table 7 Plating cycle test results of cyanide-free gold-tin alloy plating solution containing stabilizer Number of cycles Coating appearance Bath state 1 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 3 Fine crystals, uniform bright golden yellow The plating solution is clear and transparent, without precipitation 5 Fine crystallization, reduced gloss of coating The plating solution is turbid and the color becomes darker Table 8 Effect of cyanide-free gold-tin alloy plating solution electroplating cycle test From the data in Table 7 and Table 8, it can be seen that when the cyanide-free gold-tin alloy plating solution containing a stabilizer in the present application is applied to electroplating, the coating is uniform, fine and bright golden yellow in the first 8 cycles, the plating solution is clear, colorless and transparent, and no precipitation is produced; and when the cyanide-free gold-tin alloy plating solution is applied to electroplating, the coating is uniform, fine and bright golden yellow in the first 3 cycles, the plating solution is clear, colorless and transparent, and no precipitation is produced. After 3 cycles, the glossiness of the coating decreases, and the plating solution begins to become turbid; in summary, the cyanide-free gold-tin alloy plating solution with the addition of a stabilizer effectively improves the stability of the plating solution during the electroplating process, and the generated electroplating layer is crystallized and fine, with a good appearance.

[0056] Example 5 The present embodiment provides a cyanide-free gold-tin alloy plating solution containing a stabilizer, including mass concentrations of: 2 g / L 4-hydroxyphenylethylamine, 1 g / L 2-methyl-8-hydroxyquinoline, 10 g / L sodium gold chloride, 5 g / L stannous chloride dihydrate, 70 g / L sodium sulfite, 5 g / L ethylenediaminetetraacetic acid, 50 g / L potassium pyrophosphate, 60 g / L ammonium citrate, and 5 g / L hydroquinone.

[0057] In this example, the prepared cyanide-free gold-tin alloy plating solution containing a stabilizer is subjected to a performance test while introducing a cyanide-free gold-tin alloy plating solution (whose mass concentration is the same as that of the cyanide-free gold-tin alloy plating solution in Example 5, except that no stabilizer is added) as a comparison, as shown in the following.

[0058] Select a 50×50×1mm copper specimen for plating (electroplating parameters: current density 1A / dm 2 , temperature 50℃, pH value controlled between 7-8, ratio of anode to cathode area greater than 2:1, platinum-plated titanium anode is used as anode plate), replace the copper sheet every 30 minutes of electroplating. During this process, it is necessary to observe whether the state of the coating is normal, whether there is precipitation, discoloration and other abnormal conditions in the plating solution, and at the same time analyze and record the amount of main salt added to the plating solution.

[0059] The test results are shown in Tables 9 and 10, specifically: Number of cycles Coating appearance Bath state 1 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 3 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 5 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 8 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation Table 9 Plating cycle test results of cyanide-free gold-tin alloy plating solution containing stabilizer Number of cycles Coating appearance Bath state 1 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 3 Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 5 Fine crystallization, reduced gloss of coating The plating solution is turbid and the color becomes darker Table 10 Effect of cyanide-free gold-tin alloy plating cycle test From the data in Tables 9 and 10, it can be seen that when the cyanide-free gold-tin alloy plating solution containing a stabilizer in the present application is used for electroplating, the coating is uniform, delicate and bright golden yellow in the first 8 cycles, the plating solution is clear, colorless and transparent, and no precipitation is produced; and when the cyanide-free gold-tin alloy plating solution is used for electroplating, the coating is uniform, delicate and bright golden yellow in the first 3 cycles, the plating solution is clear, colorless and transparent, and no precipitation is produced. After 3 cycles, the glossiness of the coating decreases, the color of the plating solution becomes darker, and turbidity begins to appear; this may be because hydroquinone has a strong free radical capture effect, which can quickly capture the free radicals generated by the decomposition of oxygen to form a stable free radical structure, thereby preventing the further reaction of the free radicals, which can effectively inhibit Sn 2+ Oxidation reaction occurs, protecting Sn 2+ At the same time, hydroquinone also has a chain breaking effect, which can react with oxygen to make the free radicals generated by oxygen decomposition react with the loaded organic matter, thereby inhibiting the further generation and transfer of free radicals. In summary, the addition of stabilizer and hydroquinone to the cyanide-free gold-tin alloy plating solution effectively improves the stability of the plating solution during the electroplating process, and the generated electroplating layer has fine crystals and a good appearance.

[0060] Example 6 The present embodiment provides a cyanide-free gold-tin alloy plating solution containing a stabilizer, including mass concentrations of: 2 g / L 4-hydroxyphenylethylamine, 1 g / L 2-methyl-8-hydroxyquinoline, 10 g / L sodium gold chloride, 5 g / L stannous chloride dihydrate, 70 g / L sodium sulfite, 5 g / L ethylenediaminetetraacetic acid, 50 g / L potassium pyrophosphate, 60 g / L ammonium citrate, 5 g / L hydroquinone, and silicone oil, wherein the thickness of the silicone oil floating on the surface of the electrolyte is 150 nm.

[0061] In this embodiment, the prepared cyanide-free gold-tin alloy plating solution containing a stabilizer and silicone oil is added to the alloy solution, and the comparative example (whose mass concentration is the same as that of the cyanide-free gold-tin alloy plating solution in Example 6, except that silicone oil is not added) is used as a comparison to perform a performance test. Since there is less dust in a normal electroplating environment and the state of the plating solution is not easy to distinguish, a certain amount of dust is actively thrown into the electroplating pool in the test environment by means of identification, as follows: A 50×50×1mm copper test piece was selected for plating (electroplating parameters: current density 1A / dm2, temperature 50℃, pH value controlled between 7-8, anode and cathode area ratio greater than 2:1, and a platinum-plated titanium anode was used as the anode plate). The copper sheet was replaced every 30 minutes of electroplating. During this process, it was necessary to observe whether the coating state was normal, whether there was precipitation, discoloration and other abnormal conditions in the plating solution, and at the same time analyze and record the amount of main salt added in the plating solution. The dust concentration was maintained at 1000mg / m 3 .

[0062] The test results are shown in Table 11, specifically: Number of cycles Whether to add silicone oil Coating appearance Bath state 1 Add to Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 2 Add to Fine crystals, uniform bright golden yellow Colorless, clear and transparent, no precipitation 3 Not added Fine crystals, uniform bright golden yellow The plating solution is clear with a little precipitation 4 Not added Fine crystals, uniform bright golden yellow The plating solution is clear with a little precipitation From the data in Table 11, it can be seen that when the cyanide-free gold-tin alloy plating solution containing a stabilizer in this application is added with an appropriate amount of silicone oil for electroplating, the coating is uniform, delicate and bright golden yellow. Silicone oil is added in cycle 1 and cycle 2, and the plating solution is colorless, clear and transparent, without precipitation. However, silicone oil was not added in cycle 3 and cycle 4, and the plating solution was clear with a little precipitation, indicating that the plating solution was contaminated to a certain extent. This may be because the dust in the air will be adsorbed by the silicone oil, preventing the dust in the air from entering the electrolyte, thereby reducing the dust deposition on the surface of the gold-tin alloy, and also preventing the dust from reacting with the substances in the electrolyte to form precipitation.

[0063] Example 7 like Figure 1 As shown, the present invention also provides a method for preparing a gold-tin alloy plating solution, which is applied to the gold-tin alloy plating solution as described above, and comprises the following steps: S100. Weigh sodium gold chloride particles, stannous chloride dihydrate particles, stannous chloride dihydrate particles, stannous chloride dihydrate particles, potassium pyrophosphate particles, ammonium citrate, 4-hydroxyphenylethylamine particles and 2-methyl-8-hydroxyquinoline particles according to the mass ratio of the components of the gold-tin alloy plating liquid.

[0064] Wherein, the preparation of 2-methyl-8-hydroxyquinoline comprises the following steps: S111. Add o-aminophenol to o-aminophenol and stir under reflux, the weight volume ratio of o-aminophenol to hydrochloric acid is 11 g: 40 mL-60 mL, and the concentration of hydrochloric acid is 16%-20%; S112. Add the mixed solution of o-nitrophenol dropwise to step S111, reflux for 1.5h to 3h and then cool to room temperature, the weight volume ratio of o-nitrophenol to crotonaldehyde is 1g:2ml-4ml, the dropping speed is 0.15mol / h-0.25mol / h, after placing the o-aminophenol and hydrochloric acid solution in a magnetic field, add the mixed solution of o-nitrophenol and crotonaldehyde dropwise to the mixed solution, the mixed solution accelerates the reaction rate under the catalytic effect of the magnetic field, induces the Kirkendall effect, and improves the formation of the final product.

[0065] S113. After adding excess ammonia water to the mixed solution after cooling in step S112, dichloromethane is added to extract and the lower layer of solution is taken, followed by ultrasonic drying. The thermal and mechanical effects of ultrasound can accelerate the evaporation of water in the material while protecting the quality and activity of the material. The cavitation effect can promote the uniform distribution of water in the material, improve the uniformity of drying, and reduce material loss.

[0066] S114. The solvent dried in step S113 is distilled under reduced pressure, and the fraction of 149°C-155°C / 246pa is collected. After cooling, 2-methyl-8-hydroxyquinoline solid is obtained. When the 2-methyl-8-hydroxyquinoline solid is distilled under reduced pressure from the solution, ultrasonic waves are emitted into the distillation device. The vibration effect of ultrasonic waves can destroy the layered structure of the surface of the distilled liquid, increase the effective area of ​​the interface, thereby increasing the mass transfer rate between substances, increasing the activity of the reactant molecules, making the mixture have a higher separation degree, accelerating the reaction speed, and facilitating automatic control.

[0067] Specifically, the preparation of 4-hydroxyphenylethylamine comprises the following steps: S121. In the reaction apparatus, p-methoxybenzaldehyde, methanol, anhydrous sodium acetate, and nitromethane are sequentially added, wherein the addition ratio of methoxybenzaldehyde, methanol, anhydrous sodium acetate, and nitromethane is 8mol-12mol: 6L-10L: 1.5mol-2.5mol: 13mol-17mol, and the reaction is continued for 5h to 7h, and crystallization is performed at low temperature, and the crystals are filtered and dried to obtain; S122. Add the crystals obtained in step S121 to a reaction device, and then add anhydrous ethanol, concentrated hydrochloric acid and palladium carbon in sequence, and introduce hydrogen gas to react until the nitro group is completely reacted to obtain a primary solution; When methoxybenzaldehyde, methanol, anhydrous sodium acetate and nitromethane react in a reaction device, they are placed in an ultrasonic environment. The cavitation effect generated by the ultrasonic wave can produce a local high temperature and high pressure environment, increase the collision frequency and energy between the reactant molecules, thereby accelerating the rate of the chemical reaction and reducing the occurrence of thermal decomposition or side reactions.

[0068] Low-temperature freeze drying is used when drying the crystals to obtain anhydrous crystals. The volume and shape of the low-temperature dried crystals remain basically unchanged, the rehydration property is good, the original structure is maintained, and no concentration phenomenon occurs. The dried material is loose and porous, sponge-like, and dissolves quickly and completely after adding water, and the original properties are restored almost immediately.

[0069] The addition ratio of crystal, anhydrous ethanol, concentrated hydrochloric acid and palladium carbon is 0.8mol-1.2mol:9L-11L:180ML-230ML:140g-160g; S123. Filter the primary solution in step S122 to remove the catalyst, and then distill to obtain 4-hydroxyphenethylamine.

[0070] S200. Under constant temperature conditions, after adding deionized water to the mixing container, the solid particles weighed in step S100 are dissolved in the deionized water in sequence, and stirred continuously; S300. Add deionized water to the mixing container and adjust the volume to a specified concentration.

[0071] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A stabilizer for cyanide-free gold-tin alloy plating, characterized in that The invention comprises the following raw materials and weight concentrations: 4-hydroxyphenylethylamine 0.15 g / L -5 g / L; 2-Methyl-8-hydroxyquinoline 0.05g / L -2.5g / L.

2. The stabilizer for cyanide-free gold-tin alloy plating according to claim 1, characterized in that: The mass ratio of the 4-hydroxyphenylethylamine to 2-methyl-8-hydroxyquinoline is 2-3:

1.

3. A gold-tin alloy plating solution, characterized in that: The stabilizer for cyanide-free gold-tin alloy plating according to any one of claims 1 to 2 also includes the following raw materials and weight concentrations: Sodium gold chloride 5 g / L -10g / L, stannous chloride dihydrate 3g / L -5g / L, sodium sulfite 50g / L -80g / L, ethylenediaminetetraacetic acid 3g / L -7g / L, potassium pyrophosphate 30g / L -60g / L, ammonium citrate 50g / L -70g / L.

4. The gold-tin alloy plating liquid according to claim 3, characterized in that: The raw materials also include 3g / L to 7g / L of hydroquinone and silicone oil, and the thickness of the silicone oil floating on the surface of the electrolyte is 100nm to 200nm.

5. A method for preparing a gold-tin alloy plating solution, applied to the gold-tin alloy plating solution as claimed in claim 3, characterized in that: The following steps are involved: S100. Weigh sodium gold chloride particles, stannous chloride dihydrate particles, stannous chloride dihydrate particles, stannous chloride dihydrate particles, potassium pyrophosphate particles, ammonium citrate, 4-hydroxyphenylethylamine particles and 2-methyl-8-hydroxyquinoline particles according to the mass ratio of the gold-tin alloy plating liquid components; S200. Under constant temperature conditions, after adding deionized water to the mixing container, the solid particles weighed in step S100 are dissolved in the deionized water in sequence, and stirred continuously; S300. Add deionized water to the mixing container and adjust the volume to a specified concentration.

6. The method for preparing the tin-gold alloy solution according to claim 5, characterized in that: In step S100, the preparation of 2-methyl-8-hydroxyquinoline comprises the following steps: S111. Add o-aminophenol to the hydrochloric acid solution and stir under reflux, the weight volume ratio of o-aminophenol to hydrochloric acid is 11 g: 40 mL-60 mL, and the concentration of hydrochloric acid is 16%-20%; S112. Add a mixed solution of o-nitrophenol and crotonaldehyde dropwise to step S111, reflux for 1.5h to 3h and then cool to room temperature, the weight volume ratio of o-nitrophenol to crotonaldehyde is 1g: 2ml-4ml, and the dropping speed is 0.15mol / h-0.25mol / h; S113. After adding excess ammonia to the cooled mixed solution in step S112, dichloromethane was added for extraction and the lower layer of solution was removed, followed by ultrasonic drying; S114. The solvent dried in step S113 is distilled under reduced pressure, and the fraction at 149°C to 155°C / 246 Pa is collected and cooled to obtain 2-methyl-8-hydroxyquinoline solid.

7. The method for preparing the tin-gold alloy solution according to claim 6, characterized in that: In step S112, after placing the o-aminophenol and hydrochloric acid solution in a magnetic field, a mixed solution of o-nitrophenol and crotonaldehyde is added dropwise to the mixed solution.

8. The method for preparing the tin-gold alloy solution according to claim 6, characterized in that: In step S114, when the solution is distilled under reduced pressure to produce 2-methyl-8-hydroxyquinoline solid, ultrasonic waves are emitted into the distillation apparatus.

9. The method for preparing the tin-gold alloy solution according to claim 5, characterized in that: In step S100, the preparation of 4-hydroxyphenylethylamine comprises the following steps: S121. In the reaction apparatus, p-methoxybenzaldehyde, methanol, anhydrous sodium acetate, and nitromethane are sequentially added, wherein the addition ratio of methoxybenzaldehyde, methanol, anhydrous sodium acetate, and nitromethane is 8mol-12mol: 6L-10L: 1.5mol-2.5mol: 13mol-17mol, and the reaction is continued for 5h to 7h, and crystallization is performed at low temperature, and the crystals are filtered and dried to obtain; S122. Add the crystals obtained in step S121 to a reaction device, and then add anhydrous ethanol, concentrated hydrochloric acid and palladium carbon in sequence, and introduce hydrogen gas to react until the nitro group is completely reacted to obtain a primary solution; The addition ratio of crystal, anhydrous ethanol, concentrated hydrochloric acid and palladium carbon is 0.8mol-1.2mol:9L-11L:180ML-230ML:140g-160g; S123. Filter the primary solution in step S122 to remove the catalyst, and then distill to obtain 4-hydroxyphenethylamine.

10. The method for preparing a tin-gold alloy solution according to claim 8, characterized in that: In step S121, methoxybenzaldehyde, methanol, anhydrous sodium acetate, and nitromethane are reacted in an ultrasonic environment in a reaction device; In step S121, low-temperature freeze drying is used to obtain anhydrous crystals.